Kuasa Agama dalam Ruang Politik Indonesia Ditinjau dari Konsep Relasi Negara-Agama Machiavelli: The Power of Religion in Indonesian Political Space Seen from Machiavelli's Concept of State-Religion Relations - Herianto, Hubertus; Wijanarko, Robertus (Jurnal Filsafat Indonesia, 2024)
The focus of this paper is on the relationship between the state and religion in the Indonesian political space from the perspective of Machiavelli's state-religion relationship. The relationship between religion and the state in the Indonesian political space needs to be reviewed because in certain contexts religion appears to be more powerful than the state, which itself is more expansive. Machiavelli's concept of the relationship between the state and religion is the starting point for examining the relationship between the state and religion in Indonesia. This paper uses a qualitative approach accompanied by a critical analysis of Machiavelli's thoughts on the relationship between state and religion and the relationship between state and religion as it appears in the Indonesian political sphere. As a result, this paper shows that in Indonesia, religion seems to be bigger than the state in its politics. The power of religion over the state is evident in various facts that occur in society. This fact can only be overcome by curbing the influence of religion by following Machiavelli's thought. Religion is not removed from the political space of the Indonesian state, but is used as a tool that can achieve a better common life while strengthening the state.